Antiparasitic efficacy of geraniol from Apiaceae family in scabies treatment - Iman S. A. Khallaf; Lourin G. Malak; Soad A. L. Bayoumi; Salwa F. Farag; Ahmed M. Sayed; Sara A. Mohamed; Asmaa A. E. Nasr; Radwa Y. Ibrahim; Eman Maher Zahran; Gerhard Bringmann; Usama Ramadan Abdelmohsen (Scientific Reports)
Abstract Sarcoptic mange, commonly known as scabies, is a highly contagious skin condition caused by the burrowing mite Sarcoptes scabiei (Astigmata: Sarcoptinae). This parasitic disease significantly impacts livestock and human health, particularly in underserved regions. Current treatments rely on synthetic acaricides like permethrin and ivermectin, which suffer from limitations such as toxicity, resistance development, and environmental contamination. Essential oils from Apiaceae plants represent a promising natural alternative. This study reviewed 122 volatile constituents from Apiaceae plants and conducted comprehensive in silico analyses to identify potential antiparasitic agents. Geraniol emerged as a potent acaricidal candidate due to its strong binding affinity to acetylcholinesterase (AChE) (docking score: − 7.85 kcal/mol). In vitro testing revealed geraniol achieved a 100% mite mortality rate at concentrations as low as 6.25% within 15 min (LT50 = 9.5 min). In vivo studies using scabies-infected rabbits demonstrated that geraniol-treated animals exhibited complete clinical recovery by two weeks post-treatment, with disappearance of crusts, itching, and skin thickening. Histopathological examination showed near-complete skin regeneration with minimal inflammatory infiltrates, in contrast to control groups which exhibited severe lesions and active mite presence. Furthermore, geraniol-treated rabbits displayed new hair growth and improved general condition, with no observed adverse effects. These findings highlight geraniol’s potential as a safe, effective, and eco-friendly treatment for scabies, offering a 100% improvement in clinical and histological recovery within two weeks. Further research should focus on optimizing delivery systems and evaluating its efficacy in human clinical trials.